Evaluation of waiting time for outpatient services at Respira Hospital Yogyakarta using discrete system simulation - Astanti, Yuli Dwi; Rahmawati, Berty Dwi; Akbar, Ahmad Taufiq; Rysnalendra, Alya Pangesti (OPSI, 2023)
The Ministry of Health of the Republic of Indonesia has established standard rules for the quality of outpatient service in hospitals. One indicator of the quality of outpatient services at a hospital is the patient's waiting time to be served either by a specialist or other services such as a pharmacy. Respira Hospital Yogyakarta is a special pulmonary and respiratory hospital in Yogyakarta that continues to improve the quality of its services. Based on the results of observations and interviews it is known that in terms of waiting time, patients at Respira Hospital Yogyakarta still have to wait to get service. Examples of queues that occur include patients waiting for a specialist doctor's examination for around 75 to 90 minutes. waiting at the pharmacy and cashier for up to 60 minutes or more. This study attempts to evaluate the waiting time for outpatient services at Respira Hospital Yogyakarta using a simulation. Based on the simulation results, it is known that the patient's waiting time in the system is 217.33 minutes and the longest waiting time is in the pediatric polyclinic and pharmacy departments. After the scenario implementation were made, namely in the pediatric polyclinic and pharmacy sections, the waiting time decreased to 177.19 minutes. This means that evaluations carried out using simulations can help hospitals reduce waiting time for outpatients